Incidence and Factors Associated with Burnout in Anesthesiology: A Systematic Review. (28th November 2017) - Sanfilippo, Filippo; Noto, Alberto; Foresta, Grazia; Santonocito, Cristina; Palumbo, Gaetano J.; Arcadipane, Antonio; Maybauer, Dirk M.; Maybauer, Marc O.
Abstract : Background . Burnout syndrome has reached epidemic levels among physicians (reported around 50%). Anesthesiology is among the most stressful medical disciplines but there is paucity of literature as compared with others. Analysis of burnout is essential because it is associated with safety and quality of care. We summarize evidence on burnout in anesthesiology. Methods . We conducted a systematic review (MEDLINE up to 30.06.2017). We included studies reporting burnout in anesthesiology with no restriction on role or screening test used. Results . Fifteen surveys/studies described burnout in anesthesiology, including different workers profiles (nurses, residents, consultants, and directors). All studies used the Maslach Burnout Inventory test but with significant differences for risk stratification. Burnout prevalence greatly varied across studies (10%–41% high risk, up to 59% at least moderate risk). Factors most consistently associated with burnout were strained working pattern, working as younger consultant, and having children. There was no consistent relationship between burnout and hospital characteristics, gender, or marital status. Conclusions . Burnout prevalence among anesthesiologists is relatively high across career stages, and some risk factors are reported frequently. However, the small number of studies as well as the large differences in their methodology and in reporting approach warrants further research in this field.